Latihan Goal Setting pada Siswa Sekolah Khusus Olahraga (SKO) Riau - Alficandra, Alficandra; Ruzain, Raihanatu Binqalbi; Zulkifli, Zulkifli; Shiddiqy, Arsy Ash; Hamdi, Al Hilal; Prisilia, Karen (Jurnal Pengabdian Masyarakat (ABDIRA), 2026)
Various distractions that attract students’ attention can reduce concentration and learning motivation, which in turn affects performance in Physical Education learning. In response to this low level of motivation, Physical Education teachers need to foster students’ learning motivation through goal-setting training. Based on an agreement with the Community Service team, the proposed solutions include helping students identify their future goals, strengthening their self-confidence, and engaging them in educational games in which students are asked to write down the goals they want to achieve. The activity is followed by the creation of a “hope tree” as a reflection of positive daily activities that students can consistently practice. The methods used in this program include lectures, demonstrations, discussions, and evaluations. The results of this Community Service activity indicate an increase in participants’ knowledge of the role of goal-setting training and provide practical strategies that can be applied in the teaching and learning process to prevent boredom.